Taxation and business environment as drivers of foreign direct investment in OECD countries - Hajkova, Dana (OECD Publishing, 2007)
How important are differences in corporate taxation for the investment decisions of multinational enterprises (MNEs)? Over the past decade, interest in this issue has been growing in parallel with the increasing mobility of capital and internationalisation of businesses. Standard models of the MNEs predict that corporate taxation can influence foreign direct investment (FDI) by creating a wedge between the pre- and post-tax returns on investment. The relevant tax wedge, however, depends on whether MNEs' investment is incremental or involves the creation of entirely new plants